A soft patellar tendon on ultrasound elastography is associated with pain and functional deficit in volleyball players. Issue 5 (May 2016) - Ooi, Chin Chin; Richards, Paula J.; Maffulli, Nicola; Ede, David; Schneider, Michal E.; Connell, David; Morrissey, Dylan; Malliaras, Peter
Abstract: Objectives: To investigate the diagnostic performance of grey scale Ultrasound (US), power Doppler (PD) and US elastography for diagnosing painful patellar tendinopathy, and to establish their relationship with Victorian Institute of Sport Assessment-Patella (VISA-P) scores in a group of volleyball players with and without symptoms of patellar tendinopathy. Design: Cross-sectional study. Methods: Thirty-five volleyball players (70 patellar tendons) were recruited during a national university volleyball competition. Players were imaged with conventional US followed by elastography. The clinical findings of painful patellar tendons were used as the reference standard for diagnosing patellar tendinopathy. In addition, all participants completed the VISA-P questionnaires. Results: Of the 70 patellar tendons, 40 (57.1%) were clinically painful. The diagnostic accuracy of grey scale US, PD and elastography were 60%, 50%, 62.9%, respectively, with sensitivity/specificity of 72.5%/43.3%, 12.5%/100%, and 70%/53.3%, respectively. Combined US elastography and grey scale imaging achieved 82.5% sensitivity, 33.3% specificity and 61.4% accuracy while routine combination technique of PD and grey scale imaging revealed 72.5% sensitivity, 43.3% specificity and 60.0% accuracy. Tendons in players categorized as soft on elastography had statistically significantly greater AP thickness ( p  < 0.001) and lower VISA-P scores ( p  = 0.004) than those categorized as hard. There was no significant association between grey scale US abnormalities (hypoechogenicities and/or fusiform swelling) and VISA-P scores ( p  = 0.098). Conclusions: Soft tendon properties depicted by US elastography may be more related to patellar tendon symptoms compared to grey scale US abnormalities. The supplementation of US elastography to conventional US may enhance the sensitivity for diagnosing patellar tendinopathy in routine clinical practice.